Don Troiani's Campaign to Saratoga - 1777 : The Turning Point of the Revolutionary War in Paintings, Artifacts, and Historical Narrative /: The Turning Point of the Revolutionary War in Paintings, Artifacts, and Historical Narrative. (2019) - Troiani, Don; Schnitzer, Eric H
No abstract available